Standalone bio-interventional uveoscleral outflow enhancement for intraocular pressure reduction in open-angle glaucoma: One-year results from a prospective multicenter real-world evidence study (NCT05506423) - George Reiss; Brian Francis; Quang Nguyen; Reena Garg; Tsontcho Ianchulev; Sandra Sieminski; Paul Singh (PLoS ONE, 2026)
This prospective, multicenter, real-world evidence study evaluates the 12-month safety and effectiveness of standalone cyclodialysis with AlloFlo™ cleft reinforcement for intraocular pressure (IOP) reduction in open-angle glaucoma (OAG). AlloFlo represents the world’s first acellular, allogenic scleral tissue implant, and data from this CREST Study cohort (NCT05506423) contribute critical 12 month safety and effectiveness knowledge to the field of extracellular matrix biomaterials research, in addition to describing a novel procedure for surgical management of OAG. Eyes with investigator-confirmed inadequately controlled OAG were treated with standalone cyclodialysis using a microsurgical cannula (CycloPen™), followed by uveoscleral cleft reinforcement with AlloFlo. Eyes were followed prospectively for 12 months. Key outcomes included changes in medicated IOP, number of glaucoma medications, adverse events, and progression to subsequent glaucoma procedures. Forty-one eyes of 38 patients were included. Most eyes (66%) were considered treatment-refractory, defined as having any of: failed ≥ 1 incisional surgery or cilioablative procedure; condition in which incisional surgery would be more likely to fail than in eyes with uncomplicated OAG. At 12 months, mean IOP decreased 31% to 14.7 ± 6.9 mmHg (within the normal IOP range of 10–20 mmHg, p < 0.001); mean number of glaucoma medications decreased 32% to 1.9 ± 1.6 (p < 0.001). Seventy-one percent of eyes achieved ≥ 20% IOP reduction (a clinically meaningful benchmark set by the FDA). More than half of eyes (53%) achieved ≥ 20% IOP reduction without increasing medication. Three eyes (7.2%) progressed to incisional glaucoma surgery. Postoperative IOP elevations ≥ 10 mmHg occurred in 17% of eyes, most of which resolved within 30 days of the procedure. No persistent inflammation, implant rejection, clinically significant hyphema, or scaffold migration occurred. These findings suggest that uveoscleral outflow enhancement with AlloFlo provides a safe, conjunctiva-sparing option for IOP reduction in OAG, including eyes with prior surgical interventions.